Streamflow Recession Analysis Using Water Height. Issue 6 (23rd June 2020) - Jachens, E. R.; Roques, C.; Rupp, D. E.; Selker, J. S.
Abstract: Recession analysis is widely used for characterizing aquifer and basin properties based on the falling limb of the hydrograph. However, recession analysis using streamflow discharge requires a relationship (the rating curve) between simultaneous measurements of water height, h, and discharge, Q, across a wide range of flows, which is expensive to obtain, and changes in time. We leverage the relationship between h and Q (typical power law) to perform recession analysis using h directly, thus permitting identification of transient flow regimes, where only h is available. Recession analysis evaluates the rate of change in discharge, −dQ/dt, as a function of discharge, Q, in a bilogarithmic plot where the slope, b, contains information about aquifer characteristics. While values of b are not conserved when replacing Q with h, we find that the variability in values of b within and between events is captured in recession analysis for both Q and h . For example, when considering individual recessions from a large number of watersheds, a change from a smaller b at high discharge/stage to a larger b at lower discharge/stage occurs in most watersheds and suggests a transition to a more long‐lasting, and less drought‐sensitive, baseflow regime. With the advent of low‐cost reliable pressure loggers, as well as satellites that provide global reporting of river stage, recession analysis using water height expands the number of river systems where recession analysis can be conducted and provides the potential for insights into the variability of watershed drainage characteristics without the need for a discharge record. Key Points: Using water height in place of discharge for recession analysis preserves general characteristics of the recession curve An analytical expression equating the power law exponents of water height and discharge is given when the rating curve is a power law The ratio of power law exponents for individual recessions at high and low water heights can identify a transition in streamflow regimes